Effects of neuropeptide-Y on renal function and its interaction with sympathetic stimulation in conscious dogs. - Persson, Pontus B.; Ehmke, Heimo; Nafz, Benno; Lang, R.; Hackenthal, Eberhard; Nobiling, Rainer; Dietrich, M. S.; Kirchheim, Hartmut (The journal of physiology, 1991)
1. The effects of neuropeptide-Y (NPY) on renal function were investigated in conscious foxhounds. 2. Dose-response curves (n = 7) were obtained for NPY by measuring renal blood flow (RBF), glomerular filtration rate (GFR), urine excretion (VU), sodium excretion (VNa), potassium excretion (VK) and plasma renin activity (PRA) at different infusion rates. All variables decreased with increasing infusion rates except for PRA, which surprisingly did not change during the different infusion rates. 3. The influence of the non-constrictor dose of NPY at control pressure, and after servo-controlling renal arterial pressure at 80 mmHg, was determined for these parameters (n = 6). 4. This was repeated during a reflex sympathetic activation via carotid sinus hypotension, in order to quantify a possible interaction between the sympathetic transmitter and co-transmitter (n = 6). 5. The subthreshold NPY dose raised plasma NPY-like immunoreactivity (NPY-LI IR) significantly (renal venous plasma: 54 +/- 13 vs. 405 +/- 117 pg ml-1; P less than 0.05) and enhanced the pressure-dependent (80 mmHg) antidiuresis (0.48 +/- 0.06 vs. 0.24 +/- 0.02 ml min-1; P less than 0.05), antinatriuresis (46 +/- 11 vs. 25 +/- 3 mumol min-1; P less than 0.05), antikaliuresis (19 +/- 4 vs. 9 +/- 0.7 mumol min-1; P less than 0.05) and pressure-dependent renin release (0.95 +/- 0.27 vs. 3.0 +/- 1.1 ng angiotensin I ml-1 h-1; P less than 0.05). These effects are consistent with a non-uniform vasoconstrictor action of NPY in the renal vascular bed (see accompanying papers). 6. The effects of NPY plus sympathetic activation were less than the sum of the two individual effects, which may rely on a presynaptic mechanism.